2022
DOI: 10.21203/rs.3.rs-1889174/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-ENA Antibodies, ANA Patterns, Anti-ds DNA results, and Clinical Diagnosis: A Laboratory and Clinical Audit.

Abstract: Background:The diagnosis of autoimmune diseases (AID) is challenging, due to overlapping features with other non-immune disorders. Anti-nuclear antibodies (ANA) /anti-cellular antibodies are the sensitive screening tests but anti-double-stranded-deoxyribonucleic-acid-antibody (anti-ds-DNA), and anti-extractable nuclear antigens (anti-ENA) are specific for AIDs. We aimed to look at anti-ENA in our patients and correlated them with ANA patterns, anti-ds-DNA and clinical diagnosis for proper interpretation and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Among ENA, the most prevalent Ag was SSA, which was associated with coarse speckled and peripheral patterns of ANA (19). Another study also reported that coarse speckled ANA patterns are associated with SSA antibodies (22). The second most prevalent ENA antigen was SSB, which was associated with a coarse speckled pattern.…”
Section: Discussionmentioning
confidence: 91%
“…Among ENA, the most prevalent Ag was SSA, which was associated with coarse speckled and peripheral patterns of ANA (19). Another study also reported that coarse speckled ANA patterns are associated with SSA antibodies (22). The second most prevalent ENA antigen was SSB, which was associated with a coarse speckled pattern.…”
Section: Discussionmentioning
confidence: 91%